2019
DOI: 10.3390/antiox8060172
|View full text |Cite
|
Sign up to set email alerts
|

Carpinus turczaninowii Extract May Alleviate High Glucose-Induced Arterial Damage and Inflammation

Abstract: Hyperglycemia-induced oxidative stress triggers severe vascular damage and induces an inflammatory vascular state, and is, therefore, one of the main causes of atherosclerosis. Recently, interest in the natural compound Carpinus turczaninowii has increased because of its reported antioxidant and anti-inflammatory properties. We investigated whether a C. turczaninowii extract was capable of attenuating high glucose-induced inflammation and arterial damage using human aortic vascular smooth muscle cells (hASMCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…In the work by Kim et al, Carpinus turczaninowii extract has been demonstrated to attenuate high glucose-induced inflammation and arterial damage. Relevantly, authors provided mechanistic insights of the protective effects observed, as well as the identification of 15 types of phenolic compounds present in the extract (including quercetin, myricitrin, and ellagic acid) that exhibit antioxidant and anti-inflammatory properties [19].…”
mentioning
confidence: 99%
“…In the work by Kim et al, Carpinus turczaninowii extract has been demonstrated to attenuate high glucose-induced inflammation and arterial damage. Relevantly, authors provided mechanistic insights of the protective effects observed, as well as the identification of 15 types of phenolic compounds present in the extract (including quercetin, myricitrin, and ellagic acid) that exhibit antioxidant and anti-inflammatory properties [19].…”
mentioning
confidence: 99%